Epistemologi Ilmu dalam Islam dan IPTEK - Hafiza Husna (Kitabah: Jurnal Pendidikan Sosial Humaniora, 2023)
The Epistemology of science refers to the study of the origins, characteristics, and limits of knowledge. In Islam, the epistemology of science is influenced by religious teachings and philosophical views that give the framework for understanding and development of knowledge. Epistemology in Islam that emphasizes the importance of understanding, reflection, and the use of common sense in attaining knowledge. The purpose of research in this article is to find out how the epistemology of science is in Islam. The research methods used are qualitative with a library study approach. Data analysis USES Miles and Hubermen analysis models, that is, collecting data, data reduction, data prsention, and deduction drawing. Islam encourages its adherents to seek out knowledge and use it Â for the benefit of mankind. However, Islam also emphasizes the importance of ethics, morality, and justice in the use of science to avoid inflicting harm and harm on humas. With this approach, iptek development can be a positive instrument in improving the quality of life and progress of mankind, while at the same time paying attention to the islamic value of religion and justice.